2019
DOI: 10.1177/0300891619869518
|View full text |Cite
|
Sign up to set email alerts
|

Treatment strategy for brain metastases from esophageal cancer

Abstract: Background: This study aimed to examine the treatment outcomes of patients with brain metastases from esophageal cancer. Brain metastases from esophageal cancer are rare and have a poorer prognosis than brain metastases from lung and breast cancer. Methods: This study included patients who were diagnosed with and treated for esophageal cancer in our department and subsequently developed brain metastases between April 2010 and December 2014. We examined the differences in survival in patients based on receiving… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 15 publications
1
5
1
Order By: Relevance
“…However, due to the small sample size, the relatively high female-to-male ratio of 44.4% for patients with BM from SCEC in this study remains to be confirmed. The median age of the whole cohort was 59.5 years, which is similar to previous reports on ESCC and EAC (with the median age ranging from 60.7 to 65 years) (6,12). The primary tumor was mostly located in the mid-thoracic esophagus (14/18, 77.8%).…”
Section: Discussionsupporting
confidence: 84%
See 4 more Smart Citations
“…However, due to the small sample size, the relatively high female-to-male ratio of 44.4% for patients with BM from SCEC in this study remains to be confirmed. The median age of the whole cohort was 59.5 years, which is similar to previous reports on ESCC and EAC (with the median age ranging from 60.7 to 65 years) (6,12). The primary tumor was mostly located in the mid-thoracic esophagus (14/18, 77.8%).…”
Section: Discussionsupporting
confidence: 84%
“…In the present study, male patients with BM from SCEC accounted for 55.6%, with a 5:4 male-to-female ratio. This male-to-female ratio was significantly lower than expected (84-87.5%) for patients with BM from ESCC/EAC (6,11). However, due to the small sample size, the relatively high female-to-male ratio of 44.4% for patients with BM from SCEC in this study remains to be confirmed.…”
Section: Discussioncontrasting
confidence: 64%
See 3 more Smart Citations